Water supply sensitivity to climate change: An R package for implementing reservoir storage analysis in global and regional impact studies. (February 2016) - Turner, S.W.D.; Galelli, S.
Abstract: Whilst there are numerous global and regional studies of climate impacts on water resources, relatively few authors have incorporated reservoir storage into their earth system models. Consequently, such studies are unlikely to provide coherent estimates of how changes in climate might affect water supplies globally. This short communication describes an R package, named reservoir, which has been designed for rapid and easy routing of runoff data through storage. The package comprises tools for capacity design, release policy optimisation and performance analysis—allowing users to specify realistic reservoirs and then assess performance in terms of meeting water delivery targets. We demonstrate some of the capabilities of reservoir using 271 runoff records from the Global Runoff Data Centre. The package is freely available through the Comprehensive R Archive Network (CRAN). Highlights: We present R package reservoir for rapid routing of runoff through storage. Reservoir can be used for capacity design, release optimisation and simulation. Reservoir is freely available on the Comprehensive R Archive Network. Reservoir can support regional and global climate impact studies.